Potensi Penanganan Pidana Harta Benda melalui Konsep Diversi - Abdurrifai, Abdurrifai (Amsir Law Journal, 2021)
This study aimed at examining how and is it possible the setteling property crimes with the concept of diversion through the principle of restorative justice. This was the normative research, with the concept, historical, philosophy. Data were collected using the documentation studies and interviews. The sources of the data were analyzed by description, comparison, evaluation, and argumentation. The research results incicate that deliberation to reach consensus by involving victims, perpetrators and their families, law enforcement officials and third parties is the spirit of the concept of diversion through the principle of restorative justice. The deliberation proces between the prepetrator and the victim and/or the victim‘s family is carried out freely with the principle of equality and balance, so that the resulting decisions reflect justice, benefit and legal certainty. The concept of diversion through the principle of restorative justice for property crimes, has essentially been practiced customary law communities in Indonesia have long been and are still practiced, however, the Indonesian legal system or the criminal justice system has not been strictly regulated in the from of a law. The use and application and regulation are stillat a discretionary level in each law enforcement agency.